Paroxysmal Sneezing at the Onset of Syncopes and Transient Ischemic Attack Revealing a Papillary Cardiac Fibroelastoma. (17th June 2014) - Mathis, Stéphane; Lamy, Matthias; Ciron, Jonathan; Iljicsov, Anna; Arjmand, Roxana; Agius, Pierre; Neau, Jean-Philippe
Abstract : Sneezing can at times be associated with neurological disorders. The "sneeze center" is localized in the lateral medulla. We report the case of a 50-year-old man who presented three episodes of sneezing, two of them followed by an episode of transient gait instability and dizziness and the third one followed by an episode of transient left hemiparesis due to fibroelastoma of the aortic cardiac valve. To the best of our knowledge, this is the first description of a transient ischemic attack due to cardiac papillary fibroelastoma and revealed by violent episodes of sneezing.